Bulk Microstructure of Modern Composites Studied Jointly by Impulse Acoustic Microscopy and X‐ray Microtomography Techniques. Issue 12 (6th October 2019) - Levin, Vadim; Petronyuk, Yulia; Morokov, Egor; Ryzhova, Tatiana; Shanygin, Alexander; Yuan, Qingxi; Wanxia, Huang; Artyukov, Igor; Bellucci, Stefano
Abstract : Two key techniques—impulse acoustic microscopy and X‐ray microtomography—have been applied in combination for studying bulk microstructure in polymer composites whose properties critically depend on their spatial organization; nanocomposites and fiber reinforced plastics. It has been shown that the both techniques are able to represent three‐dimensional (3D) internal structure with micron resolution. The technique is based on different principles of 3D imaging and employs distinct mechanisms of contrast for microstructure displaying. In many cases, they are complementary in 3D microstructure recovering. POLYM. ENG. SCI., 59:2508–2513, 2019. © 2019 Society of Plastics Engineers